2003
DOI: 10.1046/j.1365-2672.2003.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds produced by Lactobacillus fermentum, Saccharomyces cerevisiae and Candida krusei in single starter culture fermentations of Ghanaian maize dough

Abstract: Aims: To identify and compare the volatile compounds associated with maize dough samples prepared by spontaneous fermentation and by the use of added starter cultures in Ghana. Methods and Results: The starter cultures examined were Lactobacillus fermentum, Saccharomyces cerevisiae and Candida krusei. For identification of aroma volatiles, extracts by the Likens-Nickerson simultaneous distillation and extraction technique were analysed by gas chromatography-mass spectrometry (GC-MS) and using a trained panel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 27 publications
(42 reference statements)
4
61
1
1
Order By: Relevance
“…Similar pH values from 6.3 to 4.5 was reported by Egounlety and Syarief (1992) during the studies of ogi supplemented with tempe. A pH decline with corresponding rise in acidity in maize dough fermented with and without a starter culture was also reported by Annan et al (2003). The range of pH obtained especially towards the end of fermentation was enough to inhibit the growth of undesirable microorganisms, since bacteria growth occurs optimally at pH values 6-7.…”
Section: Resultssupporting
confidence: 53%
“…Similar pH values from 6.3 to 4.5 was reported by Egounlety and Syarief (1992) during the studies of ogi supplemented with tempe. A pH decline with corresponding rise in acidity in maize dough fermented with and without a starter culture was also reported by Annan et al (2003). The range of pH obtained especially towards the end of fermentation was enough to inhibit the growth of undesirable microorganisms, since bacteria growth occurs optimally at pH values 6-7.…”
Section: Resultssupporting
confidence: 53%
“…The ability of selected microorganisms to modify taste, flavors and other characteristics of fermented products has been studied by several authors (Annan et al, 2003b, c;Mugula et al, 2003;Zorba et al, 2003;Gran et al, 2003;Ouoba et al, 2005;Azokpota, 2005). Fermentation of maize dough involving yeasts induced higher concentrations of compounds related to yeasts fermentation products such as alcohols and esters (Annan et al, 2003c). The fermentation of gowé with K. marxianus and P. anomala used singly led to a relatively higher concentration of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The absence and/or very low level of ethanol production in the L. plantarum strains and C. tropicalis mixed culture fermentation was indicative of the dominant activities of the LAB in the fermentation, as well as a contamination free process. The role of yeast in the flavour of fermented maize products has been reported by Annan et al (2003), Mugula et al (2003) and Omemu et al (2007). Therefore, the characteristic of C. tropicalis to grow in the fermentation, with little or no ethanol production, could be important in akamu production as the product flavour is an important sensory property.…”
Section: Fermentation Characteristics Ph and Titratable Acidity (Tta)mentioning
confidence: 99%
“…The simple sugars are then converted to organic acids that create the acid environment which is known to improve product stability and safety. Although yeast's main function has been related to the production of alcohol and aroma compounds that impact significantly on food quality parameters such as taste, texture, odour and nutritive value (Aidoo, Nout, & Sarkar, 2006;Annan, Poll, Sefa-Dedeh, Plahar, & Jakobsen, 2003), Omemu et al (2007) reported that yeasts associated with maize fermentation for ogi production produced several extracellular enzymes and the amylolytic activities of some of the yeasts were implicated in the breakdown of maize starch to simple sugars for other fermenting microorganisms. Contamination of cereal-based complementary foods has been implicated in diarrhoeal episodes among infants and children <5 years in developing countries.…”
Section: Introductionmentioning
confidence: 99%